1990
DOI: 10.1037/0012-1649.26.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of puberty: Adolescent, parent, and health care personnel.

Abstract: This study was designed (a) to examine relations among ratings of pubertal stage by adolescents, parents, and health care personnel, and (b) to determine if accuracy of adolescent and parent ratings varied with stage of puberty. Ss were 90 healthy adolescents: 46 boys, ages 10-15, and 44 girls, ages 9-15, and their parents. Ss were shown photos of the 5 stages of puberty (Tanner criteria). Ss rated the adolescents' pubertal stage, and a nurse practitioner completed an examination to rate the adolescents' stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 13 publications
(22 reference statements)
7
93
0
1
Order By: Relevance
“…25,26 The PDS has similarly received support in validation studies, although the evidence was clearer among girls than boys. 27 The level of agreement between measures was strong for both male and female subjects in this study, but the higher levels of agreement for female subjects are perhaps consistent with previous evidence that female subjects more accurately rate pubertal stages. Because students in Washington did not report Tanner levels, whereas both Tanner charts and the PDS were used in Victoria, it is possible that puberty might have been less precisely measured in the US sample.…”
Section: Discussionsupporting
confidence: 80%
“…25,26 The PDS has similarly received support in validation studies, although the evidence was clearer among girls than boys. 27 The level of agreement between measures was strong for both male and female subjects in this study, but the higher levels of agreement for female subjects are perhaps consistent with previous evidence that female subjects more accurately rate pubertal stages. Because students in Washington did not report Tanner levels, whereas both Tanner charts and the PDS were used in Victoria, it is possible that puberty might have been less precisely measured in the US sample.…”
Section: Discussionsupporting
confidence: 80%
“…Participants answer questions about their growth in stature and pubic hair, as well as menarche in females and voice changes in males. Dorn et al (1990) compared self-ratings and physician ratings of pubertal development and found significant correlations between adolescent self-rating and physician's rating. In our sample, levels of bioavailable testosterone correlated with selfrated pubertal stage in boys (r ϭ 0.604; p Ͻ 0.0001).…”
Section: Methodsmentioning
confidence: 99%
“…Stage of pubertal development was assessed in the parent interviews at T1 and T2 using schematic drawings of secondary gender characteristics associated with the five standard Tanner stages of pubertal development (Marshall & Tanner, 1969, 1970. Tanner stages are a widely accepted standard for assessment of physical development, and have demonstrated good reliability, validity, and parent-child agreement (Dorn, Susman, Nottelmann, Inoff-Germain, & Chrousos, 1990). The parent was provided with the (gender-appropriate) drawings, and asked to select which of them ''looked most like the child.''…”
Section: Methodsmentioning
confidence: 99%